2001
DOI: 10.1021/jf0013656
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Radical Absorbance Capacity (ORAC) and Phenolic and Anthocyanin Concentrations in Fruit and Leaf Tissues of Highbush Blueberry

Abstract: Antioxidant capacity, as measured by oxygen radical absorbance capacity (ORAC), and total phenolic and total anthocyanin contents were evaluated in fruit tissues of 87 highbush blueberry (Vacciniumcorymbosum L.) and species-introgressed highbush blueberry cultivars. ORAC and phenolic levels were evaluated in leaf tissues of the same materials. Average values for ORAC, phenolics, and anthocyanins in fruit were 15.9 ORAC units, 1.79 mg/g (gallic acid equivalents), and 0.95 mg/g (cyanidin-3-glucoside equivalents)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

35
222
21
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(285 citation statements)
references
References 16 publications
35
222
21
7
Order By: Relevance
“…The content and composition of anthocyanins in bilberries, as well as in blueberries, has been determined earlier by Suomalainen and Keränen (1961), Martinelli et al (1986), and Wang et al (2000). Several studies have also been done on the bioactive properties of bilberries and blueberries (Bomser et al, 1996;Kalt and Dufour, 1997;Youdim et al, 2000), especially concerning the antioxidant activity of their anthocyanin fractions (Prior et al, 1998;Smith et al, 2000;Ehlenfeldt and Prior, 2001). However, to our knowledge, there are no published studies on flavonoid biosynthesis in blueberries with particular regard to the expression of genes in the phenyl propanoid pathway.…”
mentioning
confidence: 98%
“…The content and composition of anthocyanins in bilberries, as well as in blueberries, has been determined earlier by Suomalainen and Keränen (1961), Martinelli et al (1986), and Wang et al (2000). Several studies have also been done on the bioactive properties of bilberries and blueberries (Bomser et al, 1996;Kalt and Dufour, 1997;Youdim et al, 2000), especially concerning the antioxidant activity of their anthocyanin fractions (Prior et al, 1998;Smith et al, 2000;Ehlenfeldt and Prior, 2001). However, to our knowledge, there are no published studies on flavonoid biosynthesis in blueberries with particular regard to the expression of genes in the phenyl propanoid pathway.…”
mentioning
confidence: 98%
“…31) In addition, previous reports have indicated that BBL contains a variety of phenolic compounds, such as chlorogenic acid, quercetin, caffeic acid, and procyanidins, and has oxygen radical absorbance capacity and antileukaemic activity. [32][33][34] Therefore, it is likely that tannin, contained in BBL, partly contributes to preventing the development of obesity-induced diseases in OLETF rats. Further investigation is necessary to characterize the active components from BBL.…”
mentioning
confidence: 99%
“…[5][6] Указанные факты делают эти соединения привлекательными с точки зрения использо-вания в качестве потенциальных антиоксидантов и пока-зывают перспективы практического применения. [7][8][9] Методы определения антиоксидантной активно-сти веществ можно разделить по способу регистрации активности потенциальных антиоксидантов на: фотоме-трические, [10][11][12][13][14][15] хемилюминесцентные, [16] волюмометри-ческие, [17] флуоресцентные, [18][19][20] электрохимические [21][22] и др. ; [23,24] по типу источника окисления и окисляемого соединения.…”
Section: Introductionunclassified